2021
DOI: 10.3390/biology10070625
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Gel in Chronic Periodontal Disease: A Randomized Clinical Trial on the Anti-Inflammatory Effects of Ozone Application

Abstract: The search for new topical treatments able to display not only antimicrobial properties but also a multiplicity of other beneficial effects while expressing safe cytocompatibility toward host tissues is being progressively developed. Antiseptics represent an aid to the gold standard nonsurgical treatment Scaling-and-Root-Planing (SRP) for periodontal disease. This split-mouth study aims to assess the efficacy of the ozonized gel GeliO3 (Bioemmei Srl, Vicenza, Italy) plus SRP (experimental treatment), with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
0
23
0
6
Order By: Relevance
“…Ozonated water and ozone have a disinfectant power, reduce the signs of inflammation, and inhibit the formation of bacteria that cause halitosis, as demonstrated by the various articles published in the literature on the use of ozone therapy in the dental field [ 10 , 11 , 12 , 13 ]. They were demonstrated to be efficacious in the management of chronic periodontitis [ 14 , 15 ] and oral lichen planus [ 16 ], without the toxic effects of dental pulp cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ozonated water and ozone have a disinfectant power, reduce the signs of inflammation, and inhibit the formation of bacteria that cause halitosis, as demonstrated by the various articles published in the literature on the use of ozone therapy in the dental field [ 10 , 11 , 12 , 13 ]. They were demonstrated to be efficacious in the management of chronic periodontitis [ 14 , 15 ] and oral lichen planus [ 16 ], without the toxic effects of dental pulp cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Em mĂ©dia concentração, pode ser usado como anti-inflamatĂłrio na endodontia, para diminuir a ação dos mediadores inflamatĂłrios intrarradiculares. JĂĄ em alta concentração, pode ser aplicado em ĂĄreas necrĂłticas, devido Ă  sua ação antimicrobiana (Tasdemir et al, 2019;Colombo et al, 2021).…”
Section: Discussionunclassified
“…Assim, as prĂĄticas integrativas e complementares em saĂșde podem exercer um papel fundamental na terapia periodontal. Dentre elas, a ozonioterapia tem crescido seu escopo de atuação na odontologia, sendo utilizada para diversos fins, mediante a concentração estabelecida (Tasdemir, Oskaybas, Alkan & Cakmak, 2019;Colombo et al, 2021).…”
Section: Introductionunclassified
“…A study carried out by Gandhi et al (2019) attested that the adjuvant use of ozonated olive oil in the treatment of chronic periodontitis significantly improves clinical and microbiological outcomes and is as effective as chlorhexidine, while being free of adverse effects. Colombo et al (2021) reported that the use of ozonated gel within a protocol for the nonsurgical treatment of periodontal disease represents a valid approach, even if without a greater effect compared to the group undergoing standard scaling and root planing plus chlorhexidine. This antimycotic efficacy of the ozonized gel is due to the oxidation of microorganisms by the slow release of peroxides (Monzillo et al, 2020).…”
Section: F Accini 2021mentioning
confidence: 99%